(untitled) (Cardiovascular Journal, 2010)
Background: The non-invasive tests like X-ray, ECG and Echocardiography are viewed as an extension of clinical art in cardiology and have become an integral part of history taking, physical examination and other diagnostic method. Atrial Septal Defect (ASD) of secundum type is defined as a through and through communication at atrial level. Previously the diagnosis and decision of surgery for ASD, mandatorily advocate cardiac catherization. Now cardiologist and cardiac surgeon very hardly asked for cardiac catheterization. Non-invasive diagnosis with the help of ECG, X-ray and Echo is sufficient for its diagnosis and treatment for surgery. In Bangladesh there is no study upon it. Considering this ground the study is perform on Bangladeshi patients. Methods: Forty six consecutive patients with clinical (auscultatory and electrocardiographic) signs of uncomplicated atrial septal defect of secundum type were examined by chest x-ray, ECG and echocardiography, before right heart catheterisation. Result: Thirty four (74%) had ASD, four patients (9%) had insignificant pulmonary stenosis, and eight subjects (17%) were normal. No false positive diagnosis of atrial septal defect was made by chest x-ray examination, whereas increased vascular markings were incorrectly interpreted as pulmonary congestion in one case. Eight patients had x-ray films showing questionable signs of left-to-right shunt. Twelve of 30 patients with a large left-to-right shunt were correctly selected for surgery based on radiological findings. Conclusion: Analysis of non invasive diagnosis and management of ASD secundum conform the usually described pattern in western literature. Keywords: Atrial Septal Defect; Cardiac Imaging DOI: 10.3329/cardio.v2i2.6645 Cardiovasc. j. 2010; 2(2) : 223-226